Low Lymphatic Vessel Density Correlates with Lymph Node Metastasis in Oral Squamous Cell Carcinoma - Dedhia, Axita (J Dent (Shiraz), 2018)
STATEMENT OF THE PROBLEM: Regional lymph nodes are the nodes draining lymph from region around the tumor and presence of metastatic tumor in regional lymph nodes is the most important prognostic factor for malignant tumors of epithelial origin. Lymphangiogenesis is associated with an increased incidence of regional lymph nodes metastasis and is possibly an essential step for metastasis. Tumor cells secrete lymphangiogenic cytokines, which results in formation of lymphatic vessels within and around the tumor and act as portals for tumor spread. PURPOSE: The present study aims to investigate and quantify lymphatic vessel density (LVD) in oral squamous cell carcinoma (OSCC) and determine whether LVD can predict the risk of sentinel lymph node metastasis. MATERIAL AND METHOD: 50 specimens of OSCC, without and with lymph node metastasis (25 each) along with 25 specimens of normal oral mucosa were assessed and LVD was quantified by D2-40 immunostaining. Discrete hotspots of intratumoral lymphatics were identified in superficial and deep areas in all carcinomas to calculate LVD. RESULTS: When compared to normal mucosa, LVD decreased in the superficial intratumoral areas and decreased further in deep areas. In addition, LVD in the superficial and deep areas of OSCC without nodal metastasis was significantly higher than that in OSCC with nodal metastasis. CONCLUSION: Our study provides evidence that lymphangiogenesis varies within the tumor. Lymphatic vessels are either compressed, collapsed, destroyed or absent in deep intratumoral region. Decrease in LVD predicts cervical lymph node metastasis both in superficial and deep areas. Lymphatics in superficial areas are probably major conduit for nodal metastasis in OSCCs.